Jesus – prophetic emissary of God - Dannhauser, Estelle (HTS teologiese studies, 2006)
The present study examines three models of research, all reaching the same conclusion, namely that Jesus was a prophet. The aim is to determine what their point of origin in research was, to determine on what basis they have grounded their research and conclusions, and to draw a comparison between both the routes they have chosen and their destinations at the end of these routes. This study likewise detects similarities between Jesus and the prophets of the Old Testament and considers the possibility that the cadre of classical prophecy may be one that describes the ministry of Jesus, if not fully, then at least to a large extent. Lastly the phenomenon of prophecy is examined to test their conclusions and to try to determine whether any research gaps that may have been left, need to be filled.